A222 EPIDEMIOLOGICAL, PHENOTYPIC AND CLINICAL PATTERNS OF EXTRAINTESTINAL MANIFESTATIONS IN INFLAMMATORY BOWEL DISEASE. (26th February 2020) - Lytvyak, E; Halloran, B; Kroeker, K; Peerani, F; Wong, K; Mason, A; Montano-Loza, A J; Baumgart, D; Dieleman, L A
Abstract: Background: Inflammatory bowel disease (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), may affect multiple organ systems. The extraintestinal manifestations (EIMs) occur frequently, considerably increase morbidity and mortality, and strongly influence the quality of life in IBD patients. Aims: To establish the all-time prevalence of EIMs in a large cohort of IBD patients and assess risk factors contributing to their development. Methods: We conducted a retrospective cohort study of IBD patients followed at the Division of Gastroenterology, University of Alberta, diagnosed between 1954 and 2019. We recorded demographic, clinical, and biochemical data. The EIMs included dermatological, musculoskeletal, ophthalmological, hepatobiliary, urogenital, and pulmonary manifestations. The chi-square and Mann-Whitney tests (median, IQR) were used to evaluate differences. Univariate logistic regression was used to determine the association of EIMs with demographic and disease-specific variables across CD and UC, with predictors (p≤0.05) further incorporated into multivariate regression models. Results: We analyzed data of 4493 IBD patients: 2354 with CD and 2139 – with UC, aged 18–96 years. Males were underrepresented in the CD cohort compared to the UC (47.8% vs 52.8%; p=0.001), with longer disease duration (16.3, IQR 16.1 vs 12.3, IQR 12.4 years; p≤0.001). The EIMs were slightly more prevalent in the CD group compared to UC (22.2% vs 20.4%; p=0.134), along with a significantly higher proportion of patients with over two EIMs (4.1% vs 1.7%; p≤0.001). The EIMs' pattern varied substantially between the IBD subtypes (Figure). In the CD cohort, the most common EIM was peripheral arthropathy (4.1%), followed by ankylosing spondylitis (4.0%) and nephrolithiasis (3.6%). Among CD patients, disease duration ≥20 years (OR 1.70, 95% CI 1.17–2.48; p=0.006), iron (OR 1.54, 95%CI 1.13–2.09; p=0.006) and calcium (OR 2.28, 95% CI 1.21–4.27; p=0.010) deficiencies were identified as risk factors for EIMs. The UC patients most frequently had primary sclerosing cholangitis (9.6%) with peripheral arthropathy and nephrolithiasis each being present in 2.2% of patients. In the UC cohort, three variables demonstrated the most significant associations with EIMs: male sex (OR 1.75, 95% CI 1.32–2.32; p≤0.001), disease duration ≥20 years (OR 1.93, 95% CI 1.35–2.74; p≤0.001), and pan-colonic disease extent (OR 2.12, 95% CI 1.03–4.36; p=0.041) (Table). Conclusions: Our data demonstrate that over one-fifth of IBD patients had at least one EIM over the course of the disease and the EIMs pattern varies substantially across CD and UC. Identification of risk factors allowing prediction of EIMs would increase awareness, assist in their early recognition, and tailor further management. Funding Agencies: AbbVie